An unusual case of extensive truncal Cutaneous larva migrans from remote area in an Indonesian adult male: A case report - Tasbun, Felix; Kusmayadi, Icha Rachmawati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Cutaneous larva migrans (CLM) is a skin disorder in the form of serpiginous spreading with erythematous and papule as a skin reaction to the invasion of hookworm. Apart from the skin infection symptoms, helminthic infections tend to most frequently involve the respiratory, gastrointestinal, neurological, and eye. We report the case of a 21-year-old male who came with erythematous papules and linear tracks in the entire body that felt itchy, especially on the abdomen and at the back. On the physical examination, there were erythematous papules, erythematous tracks in serpiginous patterns, excoriations, and erosions. The patient was diagnosed with extensive CLM. The patient was treated with oral Albendazole 400 mg once daily for 3 days, oral Cetirizine 10 mg once daily to reduce the itch, and oral Cefixime 200 mg twice daily for 3 days. At the end of the follow-up, all the lesions had resolved, and no other symptoms appeared. Extensive cases of CLM are noteworthy for the presence of Loeffler syndrome and superinfection. In remote areas, sometimes, the availability of drugs is limited. Therapy using oral Mebendazole only gives 70% resolution of the skin lesion compared to Albendazole. Combination therapy of Albendazole, antihistamines, and antibiotics gave satisfactory results.